The Strategy of Jogokariyan Mosque in Alleviating Poverty and Ignorance Through Mosque Management From The Perspective of At-Taubah:18 - Risky, Abu Risky; Betty Mauli Rosa Bustam; Andi Musthafa Husain (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2025)
The mosque serves as the center of community activities, functioning not only as a place of worship but also as a hub for social and economic empowerment. This study employs a qualitative approach using a case study method. Data collection techniques involve literature studies, where the researcher examines relevant sources to support this research. Jogokariyan Mosque implements various strategies to alleviate poverty and ignorance among its congregation. One such strategy is the regular mapping of dakwah activities to identify the specific needs of the congregation. Additionally, the mosque applies a personal approach to gain a deeper understanding of the congregation’s needs. A key initiative introduced is the Zero Balance program, ensuring that entrusted funds from the congregation are promptly distributed to those in need. Since 2005, Jogokariyan Mosque has also initiated the Independent Congregation Movement. This program encourages congregants to finance their own worship needs after calculating the cost per prayer space. This concept serves as motivation for congregants to take financial responsibility for their worship instead of relying on subsidies from others. Another strategy employed is Scenario Planning, in which the mosque management (Ta’mir) develops strategic plans to advance dakwah efforts. This planning is divided into three phases to ensure sustainable development. Through these strategies, Jogokariyan Mosque has significantly enlightened its congregation, empowering them to break free from poverty and ignorance. [Masjid merupakan pusat kegiatan umat yang tidak hanya berfungsi sebagai tempat ibadah, tetapi juga sebagai pusat pemberdayaan sosial dan ekonomi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data dilakukan melalui studi kepustakaan, di mana peneliti mencari literatur yang mendukung penelitian ini. Masjid Jogokariyan menerapkan berbagai strategi dalam mengentaskan kemiskinan dan kebodohan di kalangan jamaahnya. Salah satu strateginya adalah pemetaan dakwah yang dilakukan secara rutin untuk mengidentifikasi kebutuhan jamaah secara lebih spesifik. Selain itu, masjid menerapkan pendekatan personal guna memahami kebutuhan jamaah secara langsung. Salah satu program unggulan yang diterapkan adalah Saldo Nol, yang memastikan dana amanah dari jamaah segera tersalurkan kepada yang membutuhkan. Sejak tahun 2005, Masjid Jogokariyan juga menginisiasi Gerakan Jamaah Mandiri. Program ini bertujuan mendorong jamaah untuk membiayai sendiri kebutuhan ibadah mereka setelah dilakukan perhitungan biaya per tempat shalat. Konsep ini menjadi motivasi bagi jamaah agar tidak hanya bergantung pada subsidi orang lain dalam beribadah. Strategi lain yang diterapkan adalah Scenario Planning, di mana Ta’mir Masjid Jogokariyan merancang perencanaan strategis dalam memajukan dakwah. Perencanaan ini dibagi ke dalam tiga periode untuk memastikan pengembangan dakwah yang berkelanjutan. Dengan strategi-strategi tersebut, Masjid Jogokariyan mampu memberikan pencerahan yang signifikan kepada jamaah, sehingga membantu mereka keluar dari kemiskinan dan kebodohan.]